Analysis of viscosity measurements obtained using the short back extrusion method. Part 2: Verification of short back extrusion in viscometry. Issue 2 (20th February 2020) - Hoshino, Takayoshi
Abstract: The short back extrusion (SBE) method of the translational concentric cylinder viscometer improves upon the back extrusion (BE) method by starting from an immersed position and acting over a short distance. According to this improvement, the SBE method can measure the flow behavior consecutively in short distance movement. Also using novel mathematical formulas, the analysis program automatic determines between Newtonian, power law, and Herschel–Bulkley flow and can be presented to the constitutive equation and the graph of the flow behavior. In the first part, the theory and mathematical analyses were presented; in this second part, the verification is presented to prove the accuracy of the SBE method using viscosity standard for Newtonian flow, locust bean gum solution for power‐law flow, and commercial mayonnaise for Herschel–Bulkley flow. There are no viscosity standards in the non‐Newtonian fluid, so the SBE method analysis was compared with the cone‐plate viscometry. In special, the viscosity measurement of Herschel–Bulkley fluids using conventional cone‐plate viscometry is very difficult because of the destruction of the sample structure by the rotational measurement. The yield stress of truly starting to flow cannot be measured and only the viscosity in the destroyed state can be measured. There is no other viscometry that can easily determine the characteristics of a fluid and display constitutive equations and graphs. Recently, the oscillatory shear testing has conducted replacing cone‐plate viscometry but the SBE method can regain the right to measure viscosity of Herschel–Bulkley fluids.